Targeted cerebrospinal fluid analysis for inborn errors of metabolism on an LC-MS/MS analysis platform - Klinke, Glynis; Richter, Sylvia; Monostori, Péter; Schmidt‐Mader, Brigitte; García‐Cazorla, Angels; Artuch, Rafael; Christ, Stine; Opladen, Thomas; Hoffmann, Georg F.; Blau, Nenad; Okun, Jürgen G. (Journal of inherited metabolic disease, 2020)
Background Laboratory investigations of cerebrospinal fluid (CSF) are essential when suspecting an inborn error of metabolism (IEM) involving neurological features. Available tests are currently performed on different analytical platforms, requiring a large sample volume and long turnaround time, which often delays timely diagnosis. Therefore, it would be preferable to have an “one-instrument” targeted multi-metabolite approach. Method A liquid chromatography-tandem mass spectrometry (LC-MS/MS) platform, based on two different methods for analysing 38 metabolites using positive and negative electrospray ionisation modes, was established. To allow for platform extension, both methods were designed to use the same CSF sample preparation procedure and to be run on the same separation column (ACE C18-PFP). Results Assessment of the LC-MS/MS platform methods was first made by analytical validation, followed by the establishment of literature-based CSF cut-off values and reference ranges, and by the measurement of available samples obtained from patients with confirmed diagnoses of aromatic l-amino acid decarboxylase deficiency, guanidinoacetate methyltransferase deficiency, ornithine aminotransferase deficiency, cerebral folate deficiency and methylenetetrahydrofolate reductase deficiency. Conclusion An extendable targeted LC-MS/MS platform was developed for the analysis of multiple metabolites in CSF, thereby distinguishing samples from patients with IEM from non-IEM samples. Reference concentrations for several biomarkers in CSF are provided for the first time. By measurement on a single analytical platform, less sample volume is required (200 μL), diagnostic results are obtained faster, and preanalytical issues are reduced. Synopsis LC-MS/MS platform for CSF analysis consisting of two differentially designed methods.